2019
DOI: 10.3390/jimaging5040049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Human Photoreceptoral Inputs from Night-Time Lights Using RGB Imaging Photometry

Abstract: Night-time lights interact with human physiology through different pathways starting at the retinal layers of the eye; from the signals provided by the rods; the S-, L- and M-cones; and the intrinsically photosensitive retinal ganglion cells (ipRGC). These individual photic channels combine in complex ways to modulate important physiological processes, among them the daily entrainment of the neural master oscillator that regulates circadian rhythms. Evaluating the relative excitation of each type of photorecep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This approach seeks to reduce their excessive light emissions, especially the most detrimental ones, and is formulated basically (although not exclusively) in terms of intensive quantities, that is, indicators of relative performance. Some examples of these intensive quantities are the fraction of light emitted by a luminaire toward the upper hemisphere, the average number of lumen per square meter (lx) on the lit surfaces, the fraction of the light emitted by a lamp that effectively reaches the area intended to be illuminated (utilization factor), the luminous efficacy of the lighting system, measured in lm per W, or the relative spectral content of the light, usually described by CCT for visual purposes and by other metrics for non-visual applications (Bará et al, 2019b;Galadí-Enríquez, 2018;Lucas et al, 2014;Rea and Figueiro, 2016;Rea et al, 2012;Sánchez de Miguel et al, 2019).…”
Section: Local Sources Control: Necessary But Not Sufficientmentioning
confidence: 99%
“…This approach seeks to reduce their excessive light emissions, especially the most detrimental ones, and is formulated basically (although not exclusively) in terms of intensive quantities, that is, indicators of relative performance. Some examples of these intensive quantities are the fraction of light emitted by a luminaire toward the upper hemisphere, the average number of lumen per square meter (lx) on the lit surfaces, the fraction of the light emitted by a lamp that effectively reaches the area intended to be illuminated (utilization factor), the luminous efficacy of the lighting system, measured in lm per W, or the relative spectral content of the light, usually described by CCT for visual purposes and by other metrics for non-visual applications (Bará et al, 2019b;Galadí-Enríquez, 2018;Lucas et al, 2014;Rea and Figueiro, 2016;Rea et al, 2012;Sánchez de Miguel et al, 2019).…”
Section: Local Sources Control: Necessary But Not Sufficientmentioning
confidence: 99%
“…Salvador Bará, *1 Maria Angeles Bonmati-Carrion, 2,3 Juan Antonio Madrid, 2,3 Maria Angeles Rol, 2,3 and Jaime coefficients, in order to obtain accurate photoreceptoral input estimates. The optimum coefficients of these linear combinations can be determined by means of minimum variance estimators applied to the expected set of spectra to which persons will be exposed [4,6], or, even more generally, by directly fitting in a least-squares sense the available multispectral sensitivity curves to the photoreceptoral ones. The latter approach has the advantage of not requiring any a priori choice of an initial spectral set to build the exposure estimator.…”
Section: Multispectral Estimation Of Retinal Photoreceptoral Inputsmentioning
confidence: 99%
“…A total of 205 lamp spectra were used to compute these plots, comprising compact fluorescent, metal halide, ceramic metal-halide, T-type fluorescent, halogen, high-pressure sodium vapour, incandescent, light-emitting diodes with CCT in the range 1900÷7400 K, and mercury vapor lamps available on the market. The detailed characteristics of this lamp dataset can be found in reference [4].…”
Section: Multispectral Estimation Of Retinal Photoreceptoral Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spectral measurements are not the easiest to obtain, especially if many of them are required. It has been shown that three-band Red, Green, Blue (RGB) photometric data can be used to determine spectral indices or photoreceptor stimuli from values recorded by a Digital single-lens reflex camera (DSLR) [19,20]. This method is much faster and easier to perform.…”
Section: Introductionmentioning
confidence: 99%